Thoraco-abdominal coordination and performance during uphill running at altitude - Bernardi, Eva (PLoS One, 2017)
INTRODUCTION: Running races on mountain trails at moderate-high altitude with large elevation changes throughout has become increasingly popular. During exercise at altitude, ventilatory demands increase due to the combined effects of exercise and hypoxia. AIM: To investigate the relationships between thoraco-abdominal coordination, ventilatory pattern, oxygen saturation (SpO(2)), and endurance performance in runners during high-intensity uphill exercise. METHODS: Fifteen participants (13 males, mean age 42±9 yrs) ran a “Vertical Kilometer,” i.e., an uphill run involving a climb of approximately 1000 m with a slope greater than 30%. The athletes were equipped with a portable respiratory inductive plethysmography system, a finger pulse oximeter and a global positioning unit (GPS). The ventilatory pattern (ventilation (VE), tidal volume (VT), respiratory rate (RR), and VE/VT ratio), thoraco-abdominal coordination, which is represented by the phase angle (PhA), and SpO(2) were evaluated at rest and during the run. Before and after the run, we assessed respiratory function, respiratory muscle strength and the occurrence of interstitial pulmonary edema by thoracic ultrasound. RESULTS: Two subjects were excluded from the respiratory inductive plethysmography analysis due to motion artifacts. A quadratic relationship between the slope and the PhA was observed (r = 0.995, p = 0.036). When the slope increased above 30%, the PhA increased, indicating a reduction in thoraco-abdominal coordination. The reduced thoraco-abdominal coordination was significantly related to reduced breathing efficiency (i.e., an increased VE/VT ratio; r = 0.961, p = 0.038) and SpO(2) (r = -0.697, p<0.001). Lower SpO(2) values were associated with lower speeds at 20%≥slope≤40% (r = 0.335, p<0.001 for horizontal and r = 0.36, p<0.001 for vertical). The reduced thoraco-abdominal coordination and consequent reduction in SpO(2) were associated with interstitial pulmonary edema. CONCLUSION: Reductions in thoraco-abdominal coordination are associated with a less efficient ventilatory pattern and lower SpO(2) during uphill running. This fact could have a negative effect on performance.